Ovalbumin-mediated synthesis and simultaneous functionalization of graphene with increased protein stability - Ullah, Riaz; Khan, Shadab Ali; Aladresi, Aref Ali Mohammed; Alharbi, Sulaiman Ali; Chinnathambi, Arunachalam (Green Chemistry Letters and Reviews, 2020)
In this article, we have shown an easy, one-step, protein-directed approach for the synthesis of water-soluble and functional graphene using ovalbumin. The obtained ovalbumin functionalized graphene was characterized by UV-visible spectroscopy, X-ray diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy. Atomic force microscopy was used to check the attachment/functionalization of ovalbumin on grapheme sheets. It was shown that the functionalization of ovalbumin on grapheme sheets makes the protein more thermally stable compare to free ovalbumin, which has been shown by using sodium dodecyl sulfate polyacrylamide gel electrophoresis.
Keywords: Atomic force microscopy; graphene; graphene oxide; Ovalbumin; SDS-PAGE; thermal degradation